Addressing Academic Administration Challenges in Higher Educational Institutions through Mobile Technologies and Cloud Computing. 2021 9th International Conference on Reliability, Infocom Technologies and Optimization (Trends and Future Directions) (ICRITO) 03-04 Sep 2021Noida, India. - Tachiona Terence; Nomalanga Grootboom; Munyaradzi Zhou; Rosemary Guvhu; Vinod Kumar Shukla (IEEE, 2023)
The mushrooming of mobile technologies and the need to support academic administration whilst mobile call for a revolution. A new term has been coined in this research is Mobile Administration which refers to the use of mobile technologies in administration processes. A Mobile Administration model has been proposed in this paper which integrates the core elements of mobile technologies, applications or systems, lecturers' administrative duties, users of the mobile administration platform, theories of administration, and micro-administration. The way mobile technologies are and its uses are growing there is a need to address the demand and issue of cloud computing as well. Organizations rely on Information Technologies to complete all sorts of tasks and projects. But, it is also important to make sure that their progress is saved and stored securely and efficiently as well. This is where the cloud services come into play. Cloud computing provides on demand computing services such as storage and processing power over the internet. The research concluded that Higher Institutes of Education are not yet fully-fledged to make use of mobile administration due to lack of mobile technologies resources, lack of skills, support, and so on hence policies need to be enacted to support mobile administration. Theories of administration must be blended within mobile micro-administration processes.